Does slow release oral morphine have impact on craving and impulsivity in heroin dependent individuals?. (14th July 2022) - Giustiniani, Julie; Rothen, Stéphane; Penzenstadler, Louise; Colombo, Laura; Calzada, Gérard; Thorens, Gabriel; Zullino, Daniele
Abstract : Craving and impulsivity are addiction components which explain why heroin-dependant individuals (HDI), continue using heroin despite not wanting to do so. Opioid maintenance treatment (OMT), such as slow-release oral morphine (SROM), is the most effective treatment for opioid dependence. However, the impact of SROM on craving and impulsivity remains unclear. In this observational study, 23 HDI receiving SROM, their usual OMT, took part in the experiment. Each of the participants filled in the perceived level of craving with a visual analog scale. Their impulsivity was assessed via three laboratory tasks, the stop-signal reaction time, the Balloon Analogue Risk Task and delay discounting. Each evaluation was performed before and after SROM administration. Craving was significantly reduced after administration of SROM (difference 2.83; P  = 0.0010), whereas there were no significant differences in performance in the three laboratory tasks. In the long term, we observed an improvement on delay discounting correlated with the duration and dosage of SROM. The acute impact of SROM appears to significantly reduce craving, without impacting impulsivity. Observation of the correlation between delay discounting and the duration and dosage of OMT is of great interest and should be studied further.